2018
DOI: 10.1016/j.petrol.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical effects of oilfield chemicals on sand failure in reservoir rocks

Abstract: Sand failure may result in the production of formation sand at the same time the formation fluids are being produced. This work examines the effects of some commonly used oilfield chemicals, specifically, biocide, corrosion inhibitor and scale inhibitor, on the geomechanical strength of reservoir rocks such as limestone and sandstone. A combination of rock mechanical testing, grain size distribution analysis and analytical techniques are used to establish and define the effects of these chemicals on grain diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 24 publications
(27 reference statements)
2
26
0
Order By: Relevance
“…This could be explained by the fact that the carbonates have less favorable mechanical properties due to low degree of lithification (Durmeková et al 2003). Wuyep et al (2018) found an 18, 44 and 55% reduction in the UCS of sandstone samples from Niger Delta, Nigeria, exposed to ATMP, betaine and glutaraldehyde. When limestone samples from the same country were exposed to these chemicals under static condition, a 29 and 41% reduction in UCS was recorded in betaine and glutaraldehyde.…”
Section: Effect Of Chemicals On Unconfined Compressive Strength (Ucs)mentioning
confidence: 87%
See 4 more Smart Citations
“…This could be explained by the fact that the carbonates have less favorable mechanical properties due to low degree of lithification (Durmeková et al 2003). Wuyep et al (2018) found an 18, 44 and 55% reduction in the UCS of sandstone samples from Niger Delta, Nigeria, exposed to ATMP, betaine and glutaraldehyde. When limestone samples from the same country were exposed to these chemicals under static condition, a 29 and 41% reduction in UCS was recorded in betaine and glutaraldehyde.…”
Section: Effect Of Chemicals On Unconfined Compressive Strength (Ucs)mentioning
confidence: 87%
“…The objective of these analyses was to identify and analyze any chemical changes that might have taken place within the rock fabric and the corresponding mechanical damage to the rock fabric. The SEM, EDX and XRPD analyses were carried out as described in Wuyep et al (2018).…”
Section: Analytical Studiesmentioning
confidence: 99%
See 3 more Smart Citations